The Political Economy of Financial Regulation Policies Following the Global Crisis - Balseven, Hale (International Journal of Economics and Financial Issues, 2016)
This paper analyses the efficiency of financial regulation reforms that are being supported in a variety of theoretical approaches after the 2007/2008 global crisis. The main challenges that prevent the efficiency of the reforms are; (i) maintaining the Basel approach that is argued to have led to the financial crisis, (ii) its limited content, (iii) its lack of global and national financial infrastructure (iv) not being designed in a framework that comprises the macropolicies. Due to the reasons mentioned above, this paper argues that the regulation policy can neither fulfil its stability role nor its distributive role and that in this way, it restructures forthcoming crisis, not the financial sector. In order to prevent crises, a critical approach is required on the mode of regulation of the economy and a reorganisation of capitalism is necessary on a larger scale. Keywords: Government Policy and Regulation, Financial Crises, Crisis Management. JEL Classification: G18, G01, H12